Modulation of polar mesospheric summer echoes (PMSEs) with high-frequency heating during low solar illumination - T. L. Gunnarsdottir; A. Poggenpohl; I. Mann; A. Mahmoudian; P. Dalin; I. Haeggstroem; M. Rietveld (Annales Geophysicae, 2023)
Polar mesospheric summer echo (PMSE) formation is linked to charged dust/ice particles in the mesosphere. We investigate the modulation of PMSEs with radio waves based on measurements with EISCAT VHF radar and EISCAT heating facility during low solar illumination. The measurements were made in August 2018 and 2020 around 20:02 UT. Heating was operated in cycles with intervals of 48 s on and 168 s off. More than half of the observed heating cycles show a PMSE modulation with a decrease in PMSE when the heater is on and an increase when it is switched off again. The PMSE often increases beyond its initial strength. Less than half of the observed modulations have such an overshoot. The overshoots are small or nonexistent at strong PMSE, and they are not observed when the ionosphere is influenced by particle precipitation. We observe instances of very large overshoots at weak PMSE. PMSE modulation varies strongly from one cycle to the next, being highly variable on spatial scales smaller than a kilometer and timescales shorter than the timescales assumed for the variation in dust parameters. Average curves over several heating cycles are similar to the overshoot curves predicted by theory and observed previously. Some of the individual curves show stronger overshoots than reported in previous studies, and they exceed the values predicted by theory. A possible explanation is that the dust-charging conditions are different either because of the reduced solar illumination around midnight or because of long-term changes in ice particles in the mesosphere. We conclude that it is not possible to reliably derive the dust-charging parameters from the observed PMSE modulations.